BRANDING INDONESIA: KEBIJAKAN NEGARA DAN RESISTENSI WARGA DALAM REVITALISASI BUDAYA NASIONAL - Aminuddin, M. Faishal (Jurnal Interaktif, 2010)
The main idea of this article tend to contrast of multicultural understanding between the state and society. Brand and identityÂ  are the two identical concept. In one side there is governmentâs effort to promote a state branding. And the other side, the society drive their identity as life background. There is an interesting multicultural debate related its concept and implementation. This paper try to reviewing the debate between nationalist and globalist view in Indonesian process toward establish state branding as strategical foundation to promoting cultural diplomacy. I emphasize three characteristical surrounding Branding Indonesia as conceptual and policy framework. First, there is something problematic impact according national culture building had designed by Government in New Order regime. Second, how to manage that cultural assets can be revitalizing and do not make sense in term of under cooptation by political power. Third, Branding Indonesia can be effective if the Government works is intended to matching between civil wisdom as branding from bellow with state policy infiltration as branding from above. Keywords: Indonesia Branding; national culture, civil wisdom.